Deskripsi Permasalahan Suara pada Guru SMP Negeri di Kecamatan Banjarsari - Nanda Endriawati; Dewi Tirtawati; Kiyat Sudrajad (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Voice problems are conditions where the voice function does not function optimally due to overuse, inappropriate vokal technique, or exposure to an unfavorable environment. Junior high school teachers are a profession that relies heavily on the voice as a primary tool in the learning process. Objectives: This study aims to describe voice problems among public junior high school teachers in Banjarsari District and identify external factors, namely teaching duration and classroom noise levels. Methods: This study used a quantitative descriptive method with a sample of 66 teachers selected through purposive sampling and who had passed two screening stages. Data were collected using the Voice Handicap Index (VHI) instrument, along with information on weekly teaching duration and perceptions of classroom noise, which were analyzed univariately. Results: Based on the results of the univariate analysis, it was found that the majority of respondents, namely 58 teachers (87.9%), did not experience any impact from noise disturbances. Meanwhile, 3 teachers (4.5%) showed mild disturbances, 4 teachers (6.1%) showed moderate disturbances, and 1 teacher (1.5%) showed severe disturbances. The majority of respondents worked within the range of 20-30 hours per week, while the environmental disturbance conditions were mostly quiet. Conclusion: The majority of voice problems among public junior high school teachers in Banjarsari District were within the normal range. External factors such as teaching duration and classroom noise have the potential to impact vokal health, necessitating attention in preventing voice disorders. Keywords: Voice Problems, Junior High School Teachers, Banjarsari District.